NKT cells are necessary for maximal expression of allergic conjunctivitis(1) - Reyes, Nancy J. (Oxford University Press, 2010)
Allergic conjunctivitis (AC) is elicited by immediate hypersensitivity responses to environmental agents. It is initiated by a T(h)2-dominated immune response that is characterized by production of IgE antibodies and eosinophilic infiltration. By using an experimental mouse model of AC induced by short ragweed (SRW) pollen, we show that sensitized Jα18(−/−) mice, which lack type I NKT cells, and CD1d(−/−) mice, which lack type I and type II NKT cells, exhibited a decrease in tearing, lid edema, conjunctival edema and vasodilatation and eosinophil infiltration into the conjunctiva when compared with wild-type (WT) mice in both T(h)1- and T(h)2-prone hosts (C57BL/6 and BALB/c mice, respectively). This demonstrates that NKT cells are needed for both the early and late phases of AC. Adoptive transfer of SRW-primed CD4(+) T cells from Jα18(−/−) mice into naive WT BALB/c mice revealed that NKT cells were needed for the maximal induction of allergen-specific T(h)2 cells. Results from adoptive transfer of SRW-primed CD4(+) T cells from WT BALB/c mice to naive Jα18(−/−) mice indicated that NKT cells were also needed for the expression of AC produced by allergen-primed CD4(+) T cells. The decreased expression of AC in NKT cell-deficient mice was correlated with significant reduction in the production of T(h)2 cytokines in SRW pollen-sensitized mice compared with WT mice and in the capacity of SRW pollen-sensitized CD4(+) T cells to mediate ocular inflammation when the hosts were confronted with SRW pollen at the ocular surface.